(untitled) (The Insight, 2024)
Introduction: In recent years, there has been a notable rise in the trend of delayed childbearing. Both the average age at first childbirth and the frequency of pregnancies in advanced maternal age (AMA) have witnessed significant increases. This study aimed to evaluate pregnancy outcomes in women with advanced maternal age. Methods and materials: This cross-sectional study was carried out at the Department of Obstetrics and Gynaecology in Rangpur Medical College Hospital, Rangpur, from November 2015 to April 2016. A total of 50 patients were selected as study subjects by simple random sampling. Data cleaning, validation, and analysis were performed using the SPSS software version 16.0. Different statistical methods were adopted for this study. Result: Preeclampsia was found in 4 (21.1%) primigravida patients. Maximum patients were found cesarean section 16(84.2%). Caesarean section was found in 16(51.6%) multigravida patients, preterm labour in 2(6.5%) patients, low birth weight in 2(6.5%), preeclampsia in 16(51.6%) patients. Concerning obstetric complications, Malpresentation was found in 12(24.0%) patients, gestational hypertension in 1(2.0%) patient, and abruptio placentae in 1 (2.0%) patient. Regarding fetal outcome NICU admission patients were found in 16 (32%) patients, meconium aspiration in 7(14.0%), congenital anomaly in 2(4.0%), and perinatal loss was found in 2(2.0%). APGAR score at 1 minute <7 was found in 19(38.0%). Conclusion: The advanced age of the mother can be an independent risk factor for adverse pregnancy outcomes. Cesarean section, preterm labor, low birth weight, malpresentation, preeclampsia, meconium aspiration, and NICU admission are more frequent in the advanced maternal age group.